International Society after the Cold War: Anarchy and Order Reconsidered - Rick Fawn; Jeremy Larkins (London: Millennium Publishing Group, 1996)
'International Society after the Cold War' features contributions by leading scholars in international relations. The volume's first section explains the advent and contemporary significance of the concept of 'International society'. The second section subjects the concept to theoretical scrutiny, in terms of both its internal coherence and its applicability more broadly within the study of international relations. Chapters include discussions of liberal states and peace; sociological, political and historical limitations; diplomatic culture; and international civil society. The third section examines international society in terms of current global issues, including humanitarian intervention; the environmental crisis; European institutions; and international security.
(NP(B/11221s
Keywords: global society -- international society -- interpretation